Isolation of Chitosan Biopolymer from Nacre (Pinctada maxima) as Bone Scaffold Candidate - Taufik S, Ahmad; Alawiyah, Geby; Rahayu, Susi; Kurniawidi, Dian W; Handayana, I Gusti Ngurah Yudi; Cahyawati, Triyana Dyah; Purnaning, Dyah; Amin, Muhamad (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The rising incidence of bone injuries necessitates researching and developing safe bone replacement materials. Chitosan biopolymer is one of the available materials. Because it is non-toxic, biocompatible, and biodegradable, chitosan can be employed as a bone scaffold material. According to the European Pharmacopeia 6.0 (Eur: Ph 6.0), chitosan, with a deacetylation level of more than 70%, is safe for medicinal usage. The purpose of this research was to analyze the characteristics of chitosan isolated from nacre and the influence of nacre powder mass on the degree of deacetylation of chitosan. Chitosan was extracted by the processes of deproteination, demineralization, and deacetylation. Organoleptic tests, yield calculations for each stage, examination of the degree of deacetylation, creation of functional groups, and vibrational modes based on Fourier Transform Infrared (FTIR) data were performed on the isolated chitosan. The produced chitosan exhibited the properties of being beige color, odorless, and in powder form. The yield of insulation results obtained by the mass of chitosan. 3.7 % of the mass of nacre powder. The resultant chitosan has the formation of hydroxyl (OH) and amine (NH2) groups and vibrational stretching and bending modes. The variation in nacre powder mass throughout the isolation procedure altered the degree of deacetylation of the resultant chitosan and the wave number spectra of the hydroxyl (OH) and amine (NH2) groups. Chitosan, with a mass of 80 grams of nacre powder and a value of 76.94%, exhibited the highest degree of deacetylation. Considering that the functional groups generated in chitosan are comparable to those in bone, chitosan is a potential material for bone scaffolds.